Pengaruh metode ekstraksi biji kewer roasting dan komponen senyawa aktifnya - Mariani, Ria; Martiani, Isye; Noviyanti, Noviyanti; Avini, Fitni (Jurnal Farmasi & Sains Indonesia, 2024)
Cassia occidentalis Linn. or kewer is a plant that is commonly found in tropical and subtropical climates. Cassia occidentalis seed extract is safe for consumption after roasting the seeds and extracting them using a water solvent. Drink from the roasted seeds of this plant is known as Negro coffee or Senna coffee. In Indonesia, including the Garut area, there are communities who usually consume boiled Cassia occidentalis seeds that have been roasted as a refreshing drink. It calls kewer tea. Cassia occidentalis seeds contain phenolic compounds. Phenol compounds are one of the secondary metabolites that have antioxidant activity. Behalf of that this research aims to determine the antioxidant activity of steeping, infusion and decoction of roasted Cassia occidentalis seed powder and to analysis the active compound content of three extracts. Antioxidant activity was tested using DPPH (2,2-diphenyl-1-picrylhidrazil) method, and active compounds were identified using LC-MS/MS analyses. The results of the antioxidant activity test showed that the roasted kewer seed steeping had the highest antioxidant activity compared to the infusion and decoction, with an IC50 value of 57.864 µg/ml. The results of compound content analysis using LC-MS/MS indicated 13 compounds in the steeping, 15 compounds in the infusion, and 16 compounds in the decoction. It is suspected that compounds that play a role in antioxidant activity in steeping include flavonoids, lignans, and stilbenes, which are lost or reduced in levels in infusions and decoctions.